TO THE QUESTION OF RADIATION PROTECTION ENSURING OF PASSENGERS TAKEN RADIOPHARMACEUTICALS DURING TRANSPORTATION BY RAILWAY TRANSPORT - N. N. Artemyeva; T. B. Baltrukova (Радиационная гигиена)
The article is devoted to the issues of radiation protection provision of the passengers and employers of railway transport during transportation of passengers, taken radiopharmaceuticals. The criteria for extract of patients from hospital were considered. The characteristic of the most frequently used drugs is given. The measures for improving radiation protection of passengers and employers of railway transport during transportation of passengers, taken radiopharmaceuticals, are proposed.